2015
DOI: 10.1016/j.bpj.2015.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Two-Point Microrheology of Phase-Separated Domains in Lipid Bilayers

Abstract: Though the importance of membrane fluidity for cellular function has been well established for decades, methods for measuring lipid bilayer viscosity remain challenging to devise and implement. Recently, approaches based on characterizing the Brownian dynamics of individual tracers such as colloidal particles or lipid domains have provided insights into bilayer viscosity. For fluids in general, however, methods based on single-particle trajectories provide a limited view of hydrodynamic response. The technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…The viscosity measured for pure DPPC membranes further agrees with measurements on DPPC liposomes obtained from the fluorescence lifetime imaging of membrane-bound molecular rotors, although our value is slightly higher ( 26 , 59 ). Other studies of different mixtures have reported viscosities ranging from 2 6 1 Pa s m ( 53 , 54 , 56 58 , 60 ), in agreement with the viscosity we report for DOPC/DPPC mixtures. Finally, for pure DOPC bilayers, the range we deduce for the viscosity 0.6 1 Pa s m is consistent with the lower viscosities previously reported for DOPC membranes 0.16 0.85 1 Pa s m ( 14 , 55 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The viscosity measured for pure DPPC membranes further agrees with measurements on DPPC liposomes obtained from the fluorescence lifetime imaging of membrane-bound molecular rotors, although our value is slightly higher ( 26 , 59 ). Other studies of different mixtures have reported viscosities ranging from 2 6 1 Pa s m ( 53 , 54 , 56 58 , 60 ), in agreement with the viscosity we report for DOPC/DPPC mixtures. Finally, for pure DOPC bilayers, the range we deduce for the viscosity 0.6 1 Pa s m is consistent with the lower viscosities previously reported for DOPC membranes 0.16 0.85 1 Pa s m ( 14 , 55 ).…”
Section: Discussionsupporting
confidence: 92%
“…Finally, for pure DOPC bilayers, the range we deduce for the viscosity 0.6 1 Pa s m is consistent with the lower viscosities previously reported for DOPC membranes 0.16 0.85 1 Pa s m ( 14 , 55 ). It is noteworthy that for the mixture, we measure an intermediate viscosity between the values measured for the two homogeneous membranes, as has been found with other two-point microrheology approaches ( 60 ).…”
Section: Discussionsupporting
confidence: 80%
“…Common ways to quantitatively evaluate membrane fluidity and microviscosity, such as fluorescence correlation spectroscopy, 41 fluorescence recovery after photobleaching 42 or single particle tracking, 43 are not easily compatible with mapping large sample areas. Furthermore, their time resolution is limited, which prevents them from monitoring dynamic processes.…”
Section: Introductionmentioning
confidence: 99%
“…Interfaces between lipid bilayers and aqueous solutions are present in countless environments both natural, such as at cell and organelle membranes, and artificial, such as in suspensions of liposome-encapsulated drugs. The hydrodynamics of bilayers and bilayer-bound objects are therefore of considerable interest [1][2][3][4][5][6][7][8]. In particular, the rheology of red blood cells in vivo [9] and suspensions of cells and liposomes in vitro [10,11] depends directly on the nature of the flow boundary condition of the bilayer / water interface.…”
mentioning
confidence: 99%
“…It has been widely assumed throughout work spanning many decades that this interface is described by the no-slip condition characteristic of solidliquid interfaces [3,[12][13][14][15][16]. However, lipid bilayers are Newtonian fluids [5,7,17], and it has been speculated that their aqueous interfaces may therefore behave more like no-shear-stress boundaries, or intermediate between solid-like and liquid-like extremes [18]. Remarkably, despite its fundamental importance and widespread applicability, we are aware of almost no measurements of the flow boundary conditions at lipid bilayer surfaces.…”
mentioning
confidence: 99%